2022
DOI: 10.3390/microorganisms10071380
|View full text |Cite
|
Sign up to set email alerts
|

Current Techniques to Study Beneficial Plant-Microbe Interactions

Abstract: Many different experimental approaches have been applied to elaborate and study the beneficial interactions between soil bacteria and plants. Some of these methods focus on changes to the plant and others are directed towards assessing the physiology and biochemistry of the beneficial plant growth-promoting bacteria (PGPB). Here, we provide an overview of some of the current techniques that have been employed to study the interaction of plants with PGPB. These techniques include the study of plant microbiomes;… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
24
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 39 publications
(24 citation statements)
references
References 247 publications
0
24
0
Order By: Relevance
“…However, one should ask how bacteria have co-evolved their hormone production and modulation systems, and how plants influence and regulate the synthesis of these bacterial hormones under different environmental conditions. This could be studied through -omic responses in both PGPB and in their associated plants [ 105 ]. In fact, it has recently been suggested that it is possible to infer causal relationships between plant microbiota, including plant growth modulating bacteria, and the desired phenotypes of plant crops [ 106 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, one should ask how bacteria have co-evolved their hormone production and modulation systems, and how plants influence and regulate the synthesis of these bacterial hormones under different environmental conditions. This could be studied through -omic responses in both PGPB and in their associated plants [ 105 ]. In fact, it has recently been suggested that it is possible to infer causal relationships between plant microbiota, including plant growth modulating bacteria, and the desired phenotypes of plant crops [ 106 ].…”
Section: Discussionmentioning
confidence: 99%
“…PGPB have been used as biofertilizers and biopesticides for decades, improving plant health and promoting plant growth while protecting them from biotic (plant pathogens, including fungi, bacteria, viruses, insects, and nematodes) and abiotic (drought, salinity, flooding, extreme temperatures, pH, light intensity, and the toxicity of accumulated heavy metals) stresses by several different mechanisms, modulating the plant metabolism at physiological, morphological, biochemical, and molecular levels. The most studied abiotic stress conditions are drought and salinity [ 3 , 4 , 10 , 11 , 13 , 24 , 25 , 26 , 27 ]. PGPB can positively affect plant development through direct or indirect mechanisms [ 13 , 24 , 25 , 26 , 28 , 29 ].…”
Section: Plant Growth-promoting Bacteria (Pgpb) and Their Mechanism O...mentioning
confidence: 99%
“…Several reviews have been published in the last few years, mostly concentrating on the mechanisms of action of PGPB and how these microorganisms act under different biotic and abiotic stress conditions [ 3 , 4 , 10 , 11 , 13 , 14 , 15 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 ]. Acinetobacter , Agrobacterium , Arthobacter , Azotobacter , Azospirillum , Bacillus , Bradyrhizobium, Burkholderia , Enterobacter , Erwinia , Frankia , Klebsiella , Micrococcus , Paenibacillus , Pseudomonas , Rhizobium , Serratia , and Thiobacillus are among the PGPB genera reported in the literature [ 13 , 15 , 23 , 24 , 26 , 36 , 37 , 38 ].…”
Section: Plant Growth-promoting Bacteria (Pgpb) and Their Mechanism O...mentioning
confidence: 99%
See 1 more Smart Citation
“…Today, there is an ever-growing list of revolutionary approaches with the suffix-omics [ 1 ] that extends beyond those derived from the central dogma, i.e., genomics, transcriptomics, proteomics, and metabolomics. The application of these technologies in plant sciences has transformed our understanding of plant–microbe interactions [ 2 ]. Since the publication of the Arabidopsis thaliana microbiome [ 3 ], providing our first detailed look at this complex microbial world, scientists around the world have revealed how plants and microbes have their own sophisticated communication networks and division of labor that is subject to selection in alternative environments [ 4 ].…”
Section: Introductionmentioning
confidence: 99%